Genetic diversity and antimicrobial activity of lactic acid bacteria in the preparation of traditional fermented potato product ‘tunta’ - Ramos E.R. (2018)
This research was supported by the Programa Nacional de Innovación para la Competitividad y Productividad (Innovate Perú), under the contract N° 223-FINCyT-IA-2013 and Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica (FON-DECYT), research project PROCYT N° 316-2011-CONCYTEC-OAJ from Peru.